2010
DOI: 10.2169/internalmedicine.49.3297
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Coronary Artery Flow Velocity Pattern as a Long-Term Predictor of Left Ventricular Function and Cardiac Events after Percutaneous Coronary Intervention in Anterior Acute Myocardial Infarction

Abstract: Background Coronary flow velocity (CFV) can be used to assess short-term left ventricular function recovery and the clinical prognosis of patients with acute myocardial infarction (AMI). We evaluated CFV as a predictor of long-term left ventricular function recovery and cardiac events in patients with anterior wall AMI. Methods and Results CFV pattern of the distal left anterior descending (LAD), wall motion score index (WMSI) and left ventricular ejection fraction (LVEF) were recorded at the points of time wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
2
0
1
Order By: Relevance
“…From the coronary flow velocity obtained in this way (Figure 1), we evaluated the presence or absence of ESRF. Early systolic reversal flow (ESRF) was defined as a coronary flow reversal showing a peak velocity 10 cm/s and duration 60 msec at early systole 3,4 (Figure 1). We also recorded diastolic deceleration time (DDT) with TTE.…”
Section: Analysis Of Coronary Flow Velocity Patternmentioning
confidence: 99%
See 1 more Smart Citation
“…From the coronary flow velocity obtained in this way (Figure 1), we evaluated the presence or absence of ESRF. Early systolic reversal flow (ESRF) was defined as a coronary flow reversal showing a peak velocity 10 cm/s and duration 60 msec at early systole 3,4 (Figure 1). We also recorded diastolic deceleration time (DDT) with TTE.…”
Section: Analysis Of Coronary Flow Velocity Patternmentioning
confidence: 99%
“…Previous studies have reported that visualization of coronary flow velocity of LAD was possible in 97% of patients. 4 A learning curve is needed to visualize coronary flow velocity of distal LAD. In addition, it is necessary to be aware that in obese patients and chronic obstructive pulmonary disease patients, it is difficult to visualize coronary flow velocity of distal LAD.…”
Section: Study Limitationsmentioning
confidence: 99%
“…[279] Αντίστοιχα και σε άλλη μελέτη με τακτική παρακολούθηση από 24 ώρες έως 3 χρόνια, η DDT αποτέλεσε προγνωστικό παράγοντα της λειτουργικότητας του μυοκαρδίου. [280] Οι Iwakura Κ και συν, καθόρισαν τα κυριότερα χαρακτηριστικά της στεφανιαίας ροής σε ασθενείς με no-reflow φαινόμενο, όπως είναι η αναστροφή και η μείωση της συστολική ροής καθώς και η ταχεία κλίση της διαστολικής ροής, που αποδόθηκαν στην αύξηση της αντίστασης στη μικροκυκλοφορίας και στη μείωση του μυοκαρδιακού όγκου αίματος. [281][282][283] Παρόμοια ευρήματα παρουσίασαν και οι Lepper W συν, μελετώντας τη στεφανιαία ροή αμέσως μετά την πρωτογενή αγγειοπλαστική και σε 24 ώρες.…”
Section: μακροσκοπικός υπολογισμός του φαινομένου της μη-επαναρροής και της εμφραχθείσας περιοχήςunclassified